Carceral pedagogy: avenging panopticism - Vella, Mary Grace (Form@re - Open Journal per la formazione in rete, 2024)
Carceral pedagogy lies at the nexus of pedagogy and penology intertwined in a complex web of disciplinarity and panopticism. The role of punishment in education through punitive education and the role of education in prison through reformative education are examined within the context of carceral pedagogy. Adopting Willis’ “learning to labour” and Bowles and Gintis’ correspondence principle, the correlation between education and employment is extended to the area of corrections. This correspondence is sustained through the school-to-work-to-prison pipeline in a vicious cycle of disciplinary control within the wider neoliberal commodification of both education and corrections. Yet, in its restorative justice approach, through power/knowledge, carceral pedagogy offers a site of resistance and liberation as it appropriates panoptical surveillance to avenge its oppressors. Pedagogia carceraria: vendicarsi del panottismo. La pedagogia penitenziaria è un campo che combina la pedagogia e la penologia, intrecciate in una complessa rete di disciplinarità e panopticismo. Il ruolo della punizione attraverso l'educazione punitiva e il ruolo dell’educazione in carcere attraverso l’educazione riformativa sono esaminati nel contesto della pedagogia penitenziaria. Adottando il principio dell’“imparare a lavorare” di Willis e il principio di corrispondenza di Bowles e Gintis, la correlazione tra educazione e lavoro viene estesa all’area della punizione. Questa corrispondenza è sostenuta attraverso il percorso scuola-lavoro-carcere in un circolo vizioso di controllo disciplinare all’interno della più ampia mercificazione neoliberale, sia dell’educazione che della correzione. Tuttavia, nel suo approccio di giustizia riparativa, attraverso il potere/conoscenza, la pedagogia penitenziaria offre un terreno di resistenza e liberazione, poiché si appropria della sorveglianza panottica per vendicarsi dei suoi oppressori.